PROGRAM UNGGULAN UNTUK PEMBERDAYAAN MASYARAKAT DALAM RANGKA PENILAIAN PERUSAHAAN MENUJU PROPER BEYOND COMPLIANCE - Jannah, Nurul; Paramitadevi, Yudith Vega; Firmansyah, Muhammad Iqbaal (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
Community development is a synergy of profit, people, and planet providing both financial and environmental achievement.Â  The Indonesian Company Performance Rating Program in Environmental Management or PROPER is an obligation for companies listed at the Indonesian stock exchange. The status of beyond compliance ranking as stated in green and gold is the main achievement for companies wanted their top program to be included in PROPER. The purpose of this study is to assess community empowerment programs that are followed by PROPER's internal-external criteria using the AHP method. The criteria used are five internal criteria and six external criteria. There are three options included in top programs such as KIPAS Park, creative ecotourism village, and energy and food independent village. The results of this study are in the form of top programs namely energy and food self-sufficient villages ranked first, KIPAS parks ranked second and creative eco-tourism villages ranked third. The range between the actual sequences is not too far, the company can carry out further analysis such as SWOT or IOOC to strengthen the argumentation about its top flagship program.